2011
DOI: 10.1080/02705060.2011.553948
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and diel variation in stream habitat use by brook trout (Salvelinus fontinalis) in a headwater stream

Abstract: Although considerable information exists on habitat use by stream salmonids, only a small portion has quantitatively examined diurnal and nocturnal habitat variation. We examined diel variation in habitat use by age-0 and age-1þ brook trout (Salvelinus fontinalis) during summer and autumn in a headwater stream in northern Pennsylvania. Habitat variables measured included cover, depth, substrate, and velocity. The most pronounced diel variation occurred in the use of cover during both seasons. Both age-0 brook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Concerning diel variation in the feeding behaviour in brown trout, previously, Bachman et al (1979) stated that brown trout yielded a bimodal (crepuscular) pattern, with a major peak at dawn and a lesser one around dusk. Indeed, in salmonids there are frequent ontogenetic changes in diel activity (Railsback et al 2005;Johnson et al 2011). Thus, Railsback et al (2005) found in age-2+ had more consistent behaviour, feeding almost exclusively during the day.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning diel variation in the feeding behaviour in brown trout, previously, Bachman et al (1979) stated that brown trout yielded a bimodal (crepuscular) pattern, with a major peak at dawn and a lesser one around dusk. Indeed, in salmonids there are frequent ontogenetic changes in diel activity (Railsback et al 2005;Johnson et al 2011). Thus, Railsback et al (2005) found in age-2+ had more consistent behaviour, feeding almost exclusively during the day.…”
Section: Discussionmentioning
confidence: 95%
“…Although intraspecific variability has recently received more attention in ecological studies (de Bello et al., ; Violle et al., ), differences among individuals are still poorly represented in studies of fish communities (Blanck & Lamouroux, ; Brandl & Bellwood, ; Goldstein & Meador, ), being restricted to marine species (Hammerschlag‐Peyer & Layman, ; Pratchett et al., ). In freshwater fish communities, most knowledge on microhabitat use is descriptive (Leal et al., ; Manna et al., ; Mazzoni et al., ) and limited to population dynamics, i.e., data of one species (Bourke et al., ; Greenberg, Bergman, & Eklöv, ; Johnson, Ross, Dropkin, & Redell, ). Furthermore, the high plasticity of stream fish was frequently approached (Manna, Rezende, & Mazzoni, ; Meyer, ; Svanbäck & Persson, ; Ward, Webster, & Hart, ), which highlighted the importance of measuring the variation in ecological traits at the intraspecific level in freshwater communities.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat condition and alteration have been shown to affect Brook Trout distribution, and interspecific microhabitat partitioning is evident in some systems (Kocovsky and Carline 2006;Johnson 2008;Johnson et al 2011). However, most of these environmental studies focus on water temperature or altitude and typically fine-scale habitat conditions (Gard and Flittner 1974;Taniguchi et al 1998;Wehrly et al 2007;Stranko et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although we detected some environments that were better suited to Brook Trout or Brown Trout, the extensive overlap of suitable conditions for Brook Trout and Brown Trout was clear. Other studies have shown microhabitat and diet partitioning among these species (Johnson 1981(Johnson , 2008Korsu et al 2010;Johnson et al 2011), and the broad scale of this analysis prevents detection of those relationships. The stream reach was the spatial unit of our analysis, and many reaches are quite long.…”
Section: Caveats and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation